Accountability and Transparency in the Public Sector : The New Zealand Experience - Cangiano, M. (Washington, D.C. : International Monetary Fund, 1996)
This paper describes the reforms introduced in the New Zealand public sector since the mid-1980s. The reforms included corporatization and privatization of most state-owned enterprises, the shift from a cash-basis to an accrual-basis accounting system and the compilation of a balance sheet for the central government and its entities, performance-based arrangements for the delivery of core government outputs; and institutional changes in expenditure control mechanisms. The paper also summarizes the impact of the reforms on government revenue and spending patterns, and discusses lessons learned from New Zealand's experience.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet